Yttrium -barium oxide as a robust photocatalyst for photocatalytic degradation of organic dyes under visible light. Issue 21 (1st November 2022) - Cao, Run-Ze; Zhang, Li-Juan; Ding, Ling-Yun; Liu, Xi-Ping; Liu, Si-Tong; Tao, Hu-Chun
Abstract: Based on the structure related to the high-temperature superconductor yttrium-barium-copper oxide, two novel high-efficiency visible light photocatalysts were created in this study. The yttrium-barium oxide (YBO) semiconductors Y2 Ba3 O6 (YB3O) and Y2 Ba4 O7 (YB4O) were prepared by a copper-free solid-phase sintering method. They were applied for the effective treatment of dye-containing wastewater by photocatalysis under visible light irradiation. The degradation efficiency of methylene blue (MB) reached more than 95% within 10 min. Stable visible light degradation of methyl orange (MO) was achieved in the presence of YB3O and YB4O. The electron spin resonance technique and active substance capture technique confirmed the presence of superoxide radicals (·O2 − ), hydroxyl radicals (·OH) and holes (hVB + ) under visible light illumination. UV–Vis diffuse reflectance spectroscopy analysis showed that the direct optical band gaps of YB3O and YB4O were 2.550 eV and 2.583 eV, respectively, which resulted in their high visible absorption at 486.27 nm and 480.06 nm. After five cycles, the recoveries of YB3O and YB4O reached 67.15% and 72.98%. Therefore, YB3O and YB4O are considered as powerful semiconductor catalysts for the photocatalytic degradation of organic dyes in wastewater. Highlights: Synthesis of yttrium -barium oxide (YBO) visible light catalyst. Y2 Ba3 O6 (YB3O) and Y2 Ba4 O7 (YB4O) show a forbidden band width of 2.550 eV and 2.583 eV respectively. The effective degradation of methylene blue was achieved within 10 min under visible light. The mineralization of the total organic carbon in the degraded solutions of both dyes reached close to 80%.